Association between soft drink, fruit juice consumption and obesity in Eastern Europe: cross-sectional and longitudinal analysis of the HAPIEE study - Garduño-Alanís, A; Malyutina, S; Pajak, A; Stepaniak, U; Kubinova, R; Denisova, D; Pikhart, H; Peasey, A; Bobak, M; Stefler, D (Journal of human nutrition and dietetics, 2020)
BACKGROUND: Fruit juice and soft drink consumption have been shown to be related to obesity. However, this relationship has not been explored in Eastern Europe. The present study aimed to assess the cross-sectional and longitudinal relationships between fruit juice, soft drink consumption and body mass index (BMI) in Eastern European cohorts. METHODS: Data from the Health, Alcohol and Psychosocial factors in Eastern Europe population-based prospective cohort study, based in Russia, Poland and the Czech Republic, were used. Intakes of sugar-sweetened beverage (SSB), artificially-sweetened beverage (ASB) and fruit juice were estimated from a food frequency questionnaire. Participant BMI values were assessed at baseline (n = 26 634) and after a 3-year follow-up (data available only for Russia, n = 5205). RESULTS: Soft drink consumption was generally low, particularly in Russia. Compared to never drinkers of SSB, participants who drank SSB every day had a significantly higher BMI in the Czech [β-coefficient = 0.28; 95% confidence interval (CI) = 0.02-0.54], Russian (β-coefficient = 1.38; 95% CI = 0.62-2.15) and Polish (β-coefficient = 0.83; 95% CI = 0.29-1.37) cohorts. Occasional or daily ASB consumption was also positively associated with BMI in all three cohorts. Results for daily fruit juice intake were inconsistent, with a positive association amongst Russians (β-coefficient = 0.75; 95% CI = 0.28-1.21) but a negative trend in the Czech Republic (β-coefficient = -0.42; 95% CI = -0.86 to 0.02). Russians participants who drank SSB or ASB had an increased BMI after follow-up. CONCLUSIONS: Our findings support previous studies suggesting that soft drink consumption (including SSBs and ASBs) is positively related to BMI, whereas our results for fruit juice were less consistent. Policies regarding these beverages should be considered in Eastern Europe to lower the risk of obesity.
Keywords: Russia; Cross-Sectional Studies; sycené nápoje; ovocné a zeleninové šťávy; Male; longitudinální studie; Obesity; následné studie; dieta - přehledy; soft drinks; Poland; Česká republika; fruit juice; obezita; Carbonated Beverages; Aged; Prospective Studies; mužské pohlaví; senioři; Follow-Up Studies; Czech Republic; Fruit and Vegetable Juices; lidé; ženské pohlaví; Humans; Body Mass Index; průřezové studie; Rusko; chování při pití; Longitudinal Studies; index tělesné hmotnosti; Drinking Behavior; body mass index; Eastern Europe; Female; Polsko; lidé středního věku; Diet Surveys; Middle Aged; prospektivní studie